Temperature cycling reliability test for a ball grid array (BGA) package using finite element analysis (FEA) - Muhammad Nubli, Zulkifli (Universiti Malaysia Perlis, 2010)
Thermal cycling test is one of the reliability test that has been used to evaluate the reliability of the solder joint interconnect in ball grid array (BGA) package. The purpose of thermal cycling test is to characterize thermomechanical failure mechanism on microelectronics package. This research utilizes the computer capability to run the thermal cycling test by using finite element analysis (FEA). FEA of thermal cycling test is done by using ANSYS™ finite element software. Quarter symmetry BGA package model is built parametrically by using APDL (ANSYS™ Parametric Design Language and Macros). Two types of analyses are used to evaluate the reliability performance of solder joints in BGA package, namely the physics based analysis and the statistical based analysis. Darveaux’s energy based fatigue model is used as the constitutive equation for solder. One of the temperature cycling conditions namely, G based on JEDEC JESD22-A104 standard is used throughout the finite element analysis. The effect of different temperature cycling condition is studied by applying different value of dwell times and ramp rates. Two screening design methods namely, Central Composite Design (CCD) and Box-Behnken Matrix Design method are used to isolate the most important factors amongst six design variables such as solder joint standoff height, printed circuited board (PCB) core thickness, PCB core-in-plane Young’s Modulus, PCB core-in-plane coefficient of thermal expansion (CTE), die thickness and mold compound thickness. The optimization process is carried out using response surface methodology (RSM) to predict appropriate variables or factors that have a significant influence on BGA package failure and their interactions. Monte Carlo simulations are used to validate the randomness of the results obtained through CCD and Box-Behnken matrix design based optimization methods. It is observed that changes in ramp rate produce significant effect in solder joint fatigue life rather than changes in dwell time, but the dwell time at high temperature (high dwell) has a negligible contribution to solder joint fatigue life. It is also found that the thickness of the mold has a significant effect on the performance of the solder joint reliability (more than 50 %) as compared to that from other factors. Besides the effect of individual factor, the interaction among factors also changes the solder joint reliability. RSM based on Box-Behnken Matrix design offers the highest characteristic solder joint fatigue life with a value of 2861 cycles or 41.1% enhancement from the initial design set. RSM based on CCD offers the best goodness-of-fit measures over RSM based on Box-Behnken Matrix design. These results show that RSM based on CCD has better accuracy in representing the sample points on response surface.